Optimization of N‐Piperidinyl‐Benzimidazolone Derivatives as Potent and Selective Inhibitors of 8‐Oxo‐Guanine DNA Glycosylase 1. (13th October 2022) - Wallner, Olov; Cázares‐Körner, Armando; Scaletti, Emma Rose; Masuyer, Geoffrey; Bekkhus, Tove; Visnes, Torkild; Mamonov, Kirill; Ortis, Florian; Lundbäck, Thomas; Volkova, Maria; Koolmeister, Tobias; Wiita, Elisée; et al.
Abstract: 8‐oxo Guanine DNA Glycosylase 1 is the initiating enzyme within base excision repair and removes oxidized guanines from damaged DNA. Since unrepaired 8‐oxoG could lead to G : C→T : A transversion, base removal is of utmost importance for cells to ensure genomic integrity. For cells with elevated levels of reactive oxygen species this dependency is further increased. In the past we and others have validated OGG1 as a target for inhibitors to treat cancer and inflammation. Here, we present the optimization campaign that led to the broadly used tool compound TH5487. Based on results from a small molecule screening campaign, we performed hit to lead expansion and arrived at potent and selective substituted N ‐piperidinyl‐benzimidazolones. Using X‐ray crystallography data, we describe the surprising binding mode of the most potent member of the class, TH8535. Here, the N ‐Piperidinyl‐linker adopts a chair instead of a boat conformation which was found for weaker analogues. We further demonstrate cellular target engagement and efficacy of TH8535 against a number of cancer cell lines. Abstract : 8‐Oxoguanine DNA glycosylase 1 (OGG1) excises oxidized guanine from DNA. Besides this role in genomic integrity maintenance, the enzyme has been implicated in transcription processes and as a target to suppress inflammation. Pharmacological modulation of OGG1 has greatly contributed to understand underlying functions of bas excision repair. Here, we report on the discovery and chemical optimization that led to widely used tool compound TH5487.